Upaya Meningkatkan Hasil Belajar Bilangan Bulat Siswa Kelas VII Melalui PBL dan Culturally Responsive Teaching - Maula, Hannan; Zaki, Humaira; Yuhasriati, Yuhasriati (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2025)
This study aims to improve the learning outcomes of seventh-grade students on the topic of integers through the application of the Problem-Based Learning (PBL) model with a Culturally Responsive Teaching (CRT) approach. This classroom action research was conducted in class VII-5 at SMP Negeri 4 Banda Aceh over two cycles, each consisting of two meetings. Data were collected at each meeting through learning outcome tests. The results show an increase in the percentage of student learning mastery from 58.06% in Cycle I to 80.65% in Cycle II. The implementation of the PBL model integrated with the CRT approach, which emphasizes local cultural elements in the learning process, has proven effective in enhancing students’ conceptual understanding and problem-solving skills. The conclusion of this research is that the combination of the PBL model with the CRT approach is effective in improving student learning outcomes on the topic of integers.